2018
DOI: 10.3390/ijerph15061147
|View full text |Cite
|
Sign up to set email alerts
|

Health and Well-Being of International University Students, and Comparison with Domestic Students, in Tasmania, Australia

Abstract: International students comprise an increasingly larger proportion of higher education students globally. Empirical evidence about the health and well-being of these students is, however, limited. We sought to examine the health and well-being of international students, primarily from Asian countries, attending the University of Tasmania, Australia, using domestic students as a comparison group. Ethics approval was given to invite (via email) all currently enrolled students to participate in the study by comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 34 publications
7
47
1
Order By: Relevance
“…What is more, studies performed by other authors confirmed that the financial situation for participants is linked with the analyzed lifestyles related to health. Additionally, according to these studies also other sociodemographic variables correlated with students' health related practices, e.g., gender, age and marital status [16,20,28,42].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…What is more, studies performed by other authors confirmed that the financial situation for participants is linked with the analyzed lifestyles related to health. Additionally, according to these studies also other sociodemographic variables correlated with students' health related practices, e.g., gender, age and marital status [16,20,28,42].…”
Section: Discussionmentioning
confidence: 93%
“…Here, foreign female students showed a higher level of life satisfaction than men. Skromanis et al [28] in their study conducted in Australia among foreign and Australian students, indicated that foreign male students had lower levels of life satisfaction. Interestingly, the research conducted in 2015 among young people in Hungary, Poland and Ukraine showed, that respondents from these three countries were satisfied with their life; however, the Polish students obtained the poorest results [44].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another study carried out on a sample of international students in northern Japan indicated that 41% of the participants had depressive symptoms (Eskanadrieh et al, 2012). Several authors have demonstrated that unlike domestic students, international students are faced with several challenges that hinder their adjustment and affect their mental health (Ogunsanya, Bamgbade, Thach, Sudhapalli, & Rascati, 2018;Skromanis et al, 2018;Yeh & Inose, 2003). A study carried out in Japan indicated that the prevalence of depressive symptoms among international students was 37.1%, which was higher than that of domes-Open Journal of Social Sciences tic students at 29% (Nguyen, Le, & Meirmanov, 2019).…”
Section: Depression and Anxiety Among International Studentsmentioning
confidence: 99%
“…1 By assessing multiple health and wellbeing topics, as opposed to single topic or population-based surveys, universities can be provided accurate data to prioritise needs. With limited comprehensive health surveys completed within Australian universities, [7][8][9] there is a need for a reliability tested and specific Australian survey tool that recognises the local context. The purpose of this study was to develop a reliable, web-based tool, to measure the health of undergraduate students in Australia.…”
mentioning
confidence: 99%